ARAH DAN PRAKTIK KATEKESE UMAT KEUSKUPAN RUTENG ABAD KE-21 - Stanislaus Efodius Harmansi; Agustinus Manfred Habur (Unika Santu Paulus Ruteng, 2022)
This study seeks to examine the direction and practice of people catechesis in the 21st century of Ruteng Diocese, namely in the period 2010-2020. The research method used is documentation. Based on theory and document study, it is known that the practice of catechesis of the people in Ruteng Diocese during the 21st century was carried out in Basic Chriatian Communities. The basic direction is the development of the Kingdom of God in various fields of life, especially in the fields of culture, education, environment, ecclesiastical structure, politics, family, lay ministry, faith and the Eucharist. Kingdom-oriented catechesis is holistic. The aim is not only to develop understanding but also to prioritize the appreciation and manifestation of faith in daily concrete actions. Therefore the process is not monologue but interactive-communicative. The method of 3 M is that the people together look at their situation, evaluate it in the light of the Scriptures, and carry out follow-up actions. The people's satisfaction with the implementation of the people catechesis has not been satisfactory because the facilitators are not creative and the lack of skill in facilitating people catechesis meetings. In the future, it is necessary to provide adequate training for these facilitators